Existence of Solutions for Schrodinger-Poisson Systems with Sign-changing Weight (Journal of Partial Differential Equations, 2011)
We study the existence of solutions for the Schrödinger-Poisson system $-Δu+u+k(x)φu=α(x)|u|^{p-1}u$, in $R^3$,  $-Δφ=k(x)u^2$, in $R^3$, where 3 ≤ p < 5, α(x) is a sign-changing function such that both the supports of α^+ and α^- may have infinite measure. We show that the problem has at least one nontrivial solution under some assumptions.
Keywords: Schrödinger-Poisson system; existence result; sign-changing weight